2012
DOI: 10.1097/ta.0b013e3182452df5
|View full text |Cite
|
Sign up to set email alerts
|

Pain and satisfaction in hospitalized trauma patients

Abstract: Results suggest that orthopedic trauma patients have a significant pain burden but are satisfied with pain treatment during the hospital stay. Efforts are needed to improve pain assessment and management and findings imply that addressing self-efficacy and depressive symptoms may decrease pain and increase satisfaction at hospital discharge. Brief educational interventions that incorporate pain coping skills and self-management techniques may be a feasible approach to improving self-efficacy in the acute care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 61 publications
4
55
0
2
Order By: Relevance
“…[6] Several previous studies showed that trauma patients reported high satisfaction with pain management. [3,19] The orthopedic injury patients were satisfied with all dimensions in pain medication including time of medication to work, amount of pain relief provided, duration of pain relief provided, a form of medication, the frequency of medication and the amount of medication. [3] This finding is consistent with a study that found that burn injury patients rated high satisfaction with pain medication.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…[6] Several previous studies showed that trauma patients reported high satisfaction with pain management. [3,19] The orthopedic injury patients were satisfied with all dimensions in pain medication including time of medication to work, amount of pain relief provided, duration of pain relief provided, a form of medication, the frequency of medication and the amount of medication. [3] This finding is consistent with a study that found that burn injury patients rated high satisfaction with pain medication.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[11,12] The pain intensity interfered with patients' daily life activities including general activity, walking, and sleeping. [3,7,[10][11][12][13][14] Previous studies showed that healthcare providers used pharmacological and/or non-pharmacological interventions to reduce acute pain. For instance, pharmacological management included the use of Fentanyl and Diclofenac.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations